Asset Management and Performance of Information System-Based Irrigation System (EPAKSI) Case Study of Cabak Irrigation Area, Temanggung Regency - Hartanto, Azis; Wahyudi, S. Imam; Soedarsono, Soedarsono (Jurnal Indonesia Sosial Sains, 2024)
The purpose of this study is to determine the process of data inputted and analyzed through the ePAKSI application, In this thesis used primary and secondary data collection methods. Secondary data as a support for primary data were obtained from the Office of the Public Works and Spatial Planning Office of Temanggung Regency and from the Office of the Food Security, Agriculture and Fisheries Office of Temanggung Regency. The results showed that the data inputted and analyzed with the ePAKSI application included data on asset types, asset names, nomenclature, dimensions and conditions ranging from assets upstream (weir) to downstream (end of the channel) of the Cabak irrigation network and the latest number of assets from field searches in the form of 3 channels, 34 buildings and 14 tertiary plots were known. The results of the evaluation of the performance assessment of the irrigation system of the Cabak Irrigation Area with the ePAKSI application obtained a total value of 63.70% in the less category (55% - 70%) with recommendations for handling needs attention from the Temanggung Regency Government. The details of the evaluation results of the performance assessment of the irrigation system of the Cabak Irrigation Area consist of physical infrastructure with a score of 59.81%, planting productivity 87.84%, supporting facilities 68.00%, personnel organization 71.20%, documentation 62.50% and water user farmer associations (GP3A / IP3A) 30.00%.